2004
DOI: 10.1177/154405910408300706
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Activation by Porphyromonas gingivalis LPS in Aggressive Periodontitis with the Use of Whole-blood Cultures

Abstract: In this study, we re-visited the issue of hyper-responsiveness of monocytes to bacterial lipopolysaccharide (LPS) in aggressive periodontitis patients. We used whole-blood cultures to compare monocyte activation by Porphyromonas gingivalis LPS between Thai subjects with generalized aggressive periodontitis and those without periodontitis. Upon stimulation with P. gingivalis LPS, expression of co-stimulatory molecules on monocytes and expression of CD69 on NK and gamma delta T-cells were analyzed by flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The latter has been shown in several studies (Fredriksson et al 1998). Some authors have reported a reduced, and others a similar or even no release of IL‐1 β from mononuclear cells after LPS stimulation in periodontitis (Garrison & Nichols 1989, Shapira et al 1994, Fokkema et al 2002, Mahanonda et al 2004). An increase in the release of IL‐1 β from mononuclear cells after LPS stimulation is reported in patients with chronic periodontal disease (McFarlane et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been shown in several studies (Fredriksson et al 1998). Some authors have reported a reduced, and others a similar or even no release of IL‐1 β from mononuclear cells after LPS stimulation in periodontitis (Garrison & Nichols 1989, Shapira et al 1994, Fokkema et al 2002, Mahanonda et al 2004). An increase in the release of IL‐1 β from mononuclear cells after LPS stimulation is reported in patients with chronic periodontal disease (McFarlane et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of APCs after stimulation with periodontal pathogens has been reported both in terms of up-regulated expression of activation markers such as HLA-DR, CD40 and CD54 (Jotwani et al 2001, Kanaya et al 2004, Mahanonda et al 2004, 2006 as well as the production of inflammatory cytokines, e.g. IL-1b, IL-6 and TNF-a (Diya et al 2008, Nares et al 2009).…”
Section: Potential Drivers Of Th17 Cells/il-17 Responses In Gingival mentioning
confidence: 99%
“…To ascertain responder cell activation, co-cultured cells were surface immunostained and analyzed by flow cytometry gating on a CD3 − and a non-apoptotic monocyte size/density profile [42]. CD40 expression was measured as a sensitive indicator of monocyte activation [43]. We observed significant CD40 upregulation on monocytes co-cultured with DR3 activated CD161 + T cells, but only marginal change in CD40 levels on monocytes co-cultured with similarly activated CD161 − T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%